Lenvatinib for the treatment of kidney cancer - Študentová, Hana; Vitásková, Denisa; Melichar, Bohuslav (Expert review of anticancer therapy, 2018)
INTRODUCTION: Sequential administration of single targeted agents has evolved as the dominant paradigm in advanced RCC treatment. Lenvatinib plus everolimus is the first combination therapy in advanced RCC to show improvement in efficacy compared to monotherapy in advanced RCC while maintaining manageable toxicity profile. Areas covered: This review gives a brief overview of the contemporary clinical data on lenvatinib including its mechanism of action, pharmacokinetics, efficacy and safety profile in combination with everolimus. The clinical applications of lenvatinib in combination with everolimus are addressed within the context of the current competitive therapeutic landscape of RCC. Expert commentary: Lenvatinib is a new VEGF receptor-targeted tyrosine kinase inhibitor approved in combination with everolimus for second-line therapy in patients with advanced renal cell carcinoma progressing on a first-line VEGF receptor-targeted tyrosine kinase inhibitor. The combination of lenvatinib with everolimus significantly improved progression-free survival compared with everolimus with a hazard ratio of 0.40 and increased objective response to 43%. Optimal sequence of therapy targeting the tumor and the immune system remains a challenge and further investigation is warranted.
Keywords: receptory vaskulárního endoteliálního růstového faktoru; Antineoplastic Combined Chemotherapy Protocols; chinoliny; Carcinoma, Renal Cell; Everolimus; Quinolines; protokoly protinádorové kombinované chemoterapie; Disease-Free Survival; nádory ledvin; karcinom z renálních buněk; Humans; lidé; přežití bez známek nemoci; fenylmočovinové sloučeniny; Receptors, Vascular Endothelial Growth Factor; Phenylurea Compounds; everolimus; Kidney Neoplasms